Original paperDosimetric characteristics of a new unit for electronic skin brachytherapy - Garcia-Martinez, Teresa; Chan, Jan-Pieter; Perez-Calatayud, Jose; Ballester, Facundo (Journal of Contemporary Brachytherapy, 2014)
Purpose: Brachytherapy with radioactive high dose rate (HDR) 192 Ir source is applied to small skin cancer lesions, using surface applicators, i.e. Leipzig or Valencia type. New developments in the field of radiotherapy for skin cancer include electronic brachytherapy. This technique involves the placement of an HDR X-ray source close to the skin, therefore combining the benefits of brachytherapy with the reduced shielding requirements and targeted energy of low energy X-rays. Recently, the Esteya ® Electronic Brachytherapy System (Esteya EBS, Elekta AB-Nucletron, Stockholm, Sweden) has been developed specifically for HDR brachytherapy treatment of surface lesions. The system provides radionuclide free HDR brachytherapy by means of a small 69.5 kV X-ray source. The purpose of this study is to obtain the dosimetric characterization required for clinical implementation, providing the detailed methodology to perform the commissioning. Material and methods: Flatness, symmetry and penumbra, percentage of depth dose (PDD), kV stability, HVL, output, spectrum, linearity, and leakage have been evaluated for a set of applicators (from 10 mm to 30 mm in diameter). Results: Flatness and symmetry resulted better than 5% with around 1 mm of penumbra. The depth dose gradient is about 7%/mm. A kV value of 68.4 ± 1.0 kV (k = 1) was obtained, in good agreement with manufacturer data (69.5 kV). HVL was 1.85 mm Al. Dose rate for a typical 6 Gy to 7 Gy prescription resulted about 3.3 Gy/min and the leakage value was < 100 µGy/min. Conclusions : The new Esteya® Electronic Brachytherapy System presents excellent flatness and penumbra as with the Valencia applicator case, combined with an improved PDD, allowing treatment of lesions of up to a depth of 5 mm in combination with reduced treatment duration. The Esteya unit allows HDR brachytherapy superficial treatment within a minimally shielded environment due its low energy.